Hemisphere asymmetries in schizophrenia - Broks, P; Burnett, R. (1987)
﻿ Previous research into everyday conception of personal relationships has been sparse and fragmented, and the various specialisms fail to deal with the broader issue of interpersonal understanding. Following review of the research and theoretical background, with particular reference to changing paradigms, a holistic approach is proposed for an exploration linking the content of explanation and reflection about relationships with the incidence of conceptualising. The methodology, employing content analysis, illustrative studies and a musical analogue, is outlined. Initially focusing on verbalised conception in the form of accounts, a procedure of 'simulated correspondence with a confidant' was employed to facilitate unrestricted disclosures in general descriptions of relationships. Three coding schemes were devised for content analysis of accounts (and for independent use in subsequent research). These pertained to: (1) specific concepts and themes; (2) explanation of interpersonal effect and significance; and (3) inter-subjectivity in accounts. Overall indications from the content analyses are that accounts are characterised by superficiality of detail and insight, and concentrate more on basic viability, and on social and visible aspects of personal relationships than on intimate and psychological aspects. The limitations of content analysis, and the deficiencies disclosed, suggest attention should be given to omission in content as much as inclusion, and also to the prior issues of motivation and the extent of relationship 'mindfulness'. A musical analogy (with particular reference to representation, knowledge and appreciation) is employed to advance the exploration beyond the linguistic aspects of conception to a more general model of relationship awareness. A second set of studies turn to (1) the frequency and occasioning of reflection on relationships; (2) reappraisal over time; (3) interest in relationships compared with other subjects of general interest; and (4) factors which disincline conscious relationship deliberation and analysis. There are indications throughout of a sex difference, with men as less reflective, less inclined to participate in providing accounts, and less interested in personal relationships. Disincentives are suggested, and a theory of 'relationship mindlessness' is discussed, connecting impoverishment of content and incidence with the late emergence of 'personal relationships' as a subject of formal scholarly enquiry in psychology. It is proposed that such mindlessness, and associated disincentives, are implicated in relationship problems, and that extension of relationship education, knowledge and interest are indicated. The practicalities and possible form of learning about relationships and consciousness-raising were explored in a trial relationship understanding course. Counter-indications for such consciousness-raising were evaluated by analogy with music appreciation.